Fontes de crescimento do valor bruto da produção de cana-de-açúcar no Nordeste do Brasil - AYRES, Veronica Sena (2024)
This paper analyzes the determinants of the growth in the gross value of sugarcane production in northeastern Brazil. The sugarcane sector in the northeast is considered one of the most important in the region, contributing to the performance of agricultural production in the producing states. The aim is to understand the historical evolution of the gross value of production and to understand the factors that conditioned the performance of the sector. The analysis period covers the years 1994 to 2022. To develop the study, the Shift-Share mathematical model was used with the decomposition of three effects: area effect, price effect and yield effect. The results obtained show a greater relevance of the price effect in the growth of the gross value of production in the states of northeastern Brazil, suggesting that market factors determine the dynamics of the sector.